Functional genetic diversity of domestic and wild American mink (Neovison vison) - Morris, Kimberley Y. (Evol Appl, 2020)
The release of domestic organisms to the wild threatens biodiversity because the introduction of domestic genes through interbreeding can negatively impact wild conspecifics via outbreeding depression. In North America, farmed American mink (Neovison vison) frequently escape captivity, yet the impact of these events on functional genetic diversity of wild mink populations is unclear. We characterized domestic and wild mink in Ontario at 17 trinucleotide microsatellites located in functional genes thought to be associated with traits affected by domestication. We found low functional genetic diversity in both mink types, as only four of 17 genes were variable, yet allele frequencies varied widely between captive and wild populations. To determine whether allele frequencies of wild populations were affected by geographic location, we performed redundancy analysis and spatial analysis of principal components on three polymorphic loci (AR, ATN1 and IGF‐1). We found evidence to suggest domestic release events are affecting the functional genetic diversity of wild mink, as sPCA showed clear distinctions between wild individuals near mink farms and those located in areas without mink farms. This is further substantiated through RDA, where spatial location was associated with genetic variation of AR, ATN1 and IGF1.